Physiological responses of sea urchin, Arbacia punctulata, exposed to temperature and lipopolysaccharides (LPS) - Nahian Fyrose Fahim; Kusum Parajuli; Israt Mishu; Sinthia Kabir Mumu; Eaint Honey Aung Win; Ahmed Mustafa (PLoS ONE, 2026)
Sea urchins are interesting creatures that play important ecological roles in the sea and are popular for their culinary and medicinal uses, which belong to phylum of Echinodermata. However, rapid environmental changes create a significant impact on marine species, including sea urchins, causing them severe stress. To address this issue, scientists are attempting to cultivate sea urchins in aquaculture to aid both conservation and commercial efforts. In this study, we aimed to investigate the physiological effects of stressors on sea urchin Arbacia punctulata , using three different stress conditions: increased temperature as a physical stressor, inoculation of lipopolysaccharides (LPS) as a chemical stressor, and a combination of both (increased temperature and LPS). We collected coelomic fluid (CF) from all the experimental groups at day 1, day 3, day 7, and day 10 and observed significant variations in the numbers of total and differential coelomocytes, namely, phagocytic cells, vibratile cells, red spherule cells, and colorless spherule cells in different stress conditions compared to controlled conditions (p < 0.05). The immune cells of sea urchins, especially phagocytic cells and red spherule cells, actively responded with LPS (4 µg/ml of CF/day). Our study also found a significant amount of protein in sea urchin’s cell free coelomic fluid exposed to increased temperature stress (p < 0.05) compared to that of control group. Both physical and chemical stressors impacted the growth and reproduction of sea urchins for long time exposure to stressors. We also observed lower gonadosomatic index (GSI) in the group exposed combined stressors: LPS inoculation (4 µg/ml of CF/day) and increased temperature (1˚C/day) in comparison with the control group (p < 0.05) at day 10.